COMPARISON OF TWO DOSAGES OF SUBMUCOSAL DEXAMETHASONE TO CONTROL POSTOPERATIVE TRISMUS AFTER SURGICAL EXTRACTION OF MANDIBULAR IMPACTED THIRD MOLAR: Submucosal Dexamethasone - Khan, Tahir Ullah; Mehmood, Tariq; Khan, Zafar Ali; Farooq, Muhammad; Ishfaq, Muhammad; Afsar, Rozi (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the post surgical effects of two different concentrations’ i.e. 4mg (milligram) and 8mg of sub mucosal dexamethasone to decrease trismus by comparing the mean decrease in interincisal distance in patients undergoing impacted mandibular third molar surgery. Study Design: Randomized controlled clinical trial. Place and Duration of Study: Outpatient department of oral and maxillofacial surgery unit, Mayo Hospital, Lahore. The study was completed in 6 months, from Jan 2012 to Jul 2012. Material and Methods: This randomized controlled clinical trial was conducted on 150 patients. Patients were divided into two groups A and B. Mean interincisal distance of all patients was recorded pre operatively and post operatively. All patients were advised to use a mouthwash clorhexidine 0.2% before surgery. Group A received 4 mg dexamethasone and group B received 8 mg dexamethasone in the buccal vestibular tissues. Standard surgical procedure was performed by the same operator under same conditions. Postoperative mean interincisal distance of all patients was recorded on day 2 (after 48 hours of surgery). Results: Average age of patients was 32.62 ± 7.86 years with minimum and maximum ages of 20 and 50 years respectively. Gender distribution was almost equal. Average “maximum interincisal” mouth opening distance was significantly higher in group B as compared to group A i.e. (36 ± 3.928 mm (millimeter) versus 26.04 ± 3.097 mm) with p-value=0.000. Conclusion: Eight mg dose of dexamethasone was statistically more significant in reducing the trismus as compare to 4mg (p-value=0.000).